Good Practices and New Perspectives in Information Systems and Technologies WorldCIST 2024, Volume 6 - Rocha, Álvaro; Adeli, Hojjat; Dzemyda, Gintautas; Moreira, Fernando; Poniszewska-Marańda, Aneta (Lecture Notes in Networks and Systems, 2024)
XXIII, 384 p. 97 illus., 75 illus. in color.